Penerapan Adaboost Pada Algoritma Viola Jones Untuk Deteksi Wajah - Meri Nova Marito Br Sipahutar, Ade Linhar, Sardo Pardingotan Sipayung (LPPM-UNIKI, 2023)
Face detection is the first step in interaction between humans such as image retrieval, tracking, face recognition and so on. Currently, face detection is a very interesting topic for research. The Viola Jones algorithm is the defacto standard for face detection. So the research was carried out using the Viola Jones algorithm. The Viola Jones algorithm has 3 contributions, namely the integral image, the second contribution of the integral image allows very fast feature evaluation by using Adaboost in feature selection and the third is the use of a cascade classifier. The research results show a precision value of 85.54% and a recall of 90.25% for the Baodataset dataset. Meanwhile, for personal data, precision was 88.42% and recall was 90.60%.